Assessment of a clean and efficient fire-extinguishing technique: Continuous and cycling discharge water mist system. (1st May 2018) - Zhou, Yang; Bu, Rongwei; Gong, Junhui; Zhang, Xiaonan; Fan, Chuangang; Wang, Xishi
Abstract: As the succedaneum of halon extinguishing agent, water mist is absolutely green, harmless, and sustainable which does not cause the ozone depletion. In order to investigate the fire extinguishment performance of water mist system with both continuous and cycling discharge modes, a series of full-scale pool fire suppression experiments (including gasoline and diesel) with the two discharge modes were conducted in a confined compartment (3 m × 3 m × 3 m) under different mechanical exhaust rates. Some characteristic parameters, such as the smoke temperature, radiative and total heat flux, fire-extinguishing time, and carbon monoxide and oxygen concentration under the influences of both water mist and mechanical ventilation, were obtained, and their variation mechanisms were analyzed in detail. The experimental results show that pool fires could be extinguished more quickly using cycling water mist with shorter turn-off time. The reduction coefficient of carbon monoxide concentration increases exponentially, while the extinguishing time of both gasoline and diesel pool fires decreases first and then increases with the ventilation rate. With cycling discharge mode, the smoke temperature and heat flux both fluctuate with alternate activation of water mist. The application of cycling discharge mode substantially improves the fire suppression efficiency, especially in the condition that the pool fire is difficult to extinguish utilizing continuous discharge mode. The cycling discharge water mist system can be applied in some ventilated spaces when mechanical ventilation is unavoidable, and is helpful for personnel security and evacuation. Highlights: Pool fire suppression efficacy of water mist using two discharges was investigated. Ventilation effect on gasoline and diesel pool fire suppression was examined. Reduction coefficient of CO concentration increases exponentially. Fire extinguishing time decreases first and then increases with exhaust rate.